A cultura de paz na grande Parangaba: saberes e vivências em mediação de conflitos - Graça, João Wilame Coelho (2018)
The present work consists of studying the experiences in Culture of Peace in Greater Parangaba through Mediation of Conflicts. It was accomplished through a non-participant observation of the work carried out at the Conflict Mediation Center of Parangaba - MPCE, located at Julio Braga Street, 161, Parangaba. The social relevance of this study is to analyze the practical unfolding of the idea of peaceful resolution of conflicts by studying mediation experiences in Greater Parangaba. We also focus on understanding how the core of conflict mediation in Parangaba helps the media in developing their leading role in resolving disputes. As members of the Movement For a Culture of Peace, the theme has special meaning for us, because it unites three elements of our esteem: Culture of Peace, Mediation of Conflicts and the neighborhood of Grande Parangaba. This study uses qualitative / quantitative methodology and works with an ethnographic approach. For the accomplishment of this thesis, in addition to extensive bibliographical research, we did survey and compilation of statistics, documentary analysis, application of questionnaires, general observations of the nucleus, interviews and focus group.